On the growing complexity of HIV-1 vaccines - Hanke, T (2010)
The development of an effective HIV-1 vaccine continues to pose a formidable challenge. While traditional approaches of live-attenuated and inactivated vaccines are either too dangerous or inefficient, modern and safer subunit vaccines are still in their infancy and struggle to cope with various aspects of HIV-1 biology, including the enormous variability of HIV-1. Three simple prophylactic candidate vaccine strategies have now been tested in human efficacy trials, with only a very marginal and yet to be confirmed success in the most recent one. Thus, HIV-1 immunological control, which may require induction of both broadly neutralizing antibodies and T cells capable of controlling multiple clades and escape variants. At protective levels, an increase in subunit vaccine design complexity is required. I argue that, by analogy to antiretroviral treatment, even a relatively complex vaccine may not only serve to prove the concept, but can be successfully deployed in countries with limited resources and infrastructure. © 2010 Future Medicine Ltd.